ROYALTY FOR THE LICENSE OF INTELLECTUAL PROPERTY RIGHTS ACCORDING TO ISLAMIC LAW - B Basrowi (Fakultas Syariah (Syari'ah Faculty ), 2019)
The purpose of this study is to describe Rolaty fees for intellectual property rights in Indonesia, according to Islamic law. The method used in writing this study is the library literature method. Data analysis using four stages, starting from data collection, data classification, data filtering, and drawing conclusions. Based on the results of the analysis, it can be concluded, first, royalties are compensation for the utilization of the Economic Rights of a Work or Related Rights Products received by the creator or the owner of the related rights. Royalty fee is a fee that must be paid periodically for the use of concepts, systems, inventions, processes, methods, logos, brands or names based on a franchise agreement, whether or not accompanied by a minimum or maximum amount of certain royalties. Second, in the rules of Shari'ah, matters relating to the distribution of business profits must be determined first at the beginning of the contract (contract). Royalty fee known in the contract or book printing cooperation agreement is an equation of profit sharing (profit) in muamalah fiqh, the size of which can not be set at the beginning except the profit ratio